The art of stage lighting - Bentham, Frederick (London, United Kingdom : Pitman Publishing Limited, 1976)
The purpose of this new edition id to put over in a readable manner the essential and increasingly technical background which provides both the disciplines and the opportunities to express oneself in the art of stage lighting.
1. Setting the scene -- 2. Auditorium and stage -- 3. The development of stage lighting -- 4. Light -- 5. Lamps -- 6. Colour -- 7. Electricity, dimmers, and distribution -- 8. Lighting control -- 9. Lighting procedure -- 10. Illumination of the stage -- 11. Painting with light -- 12. Optical projection -- 13. Equipment in common line.
Includes index.
Keywords: STAGE LIGHTING